2021
DOI: 10.3390/aerospace8100283
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Analysis of Eye Movements and Fatigue in a Simulated Glass Cockpit Environment

Abstract: Pilot fatigue is a critical reason for aviation accidents related to human errors. Human-related accidents might be reduced if the pilots’ eye movement measures can be leveraged to predict fatigue. Eye tracking can be a non-intrusive viable approach that does not require the pilots to pause their current task, and the device does not need to be in direct contact with the pilots. In this study, the positive or negative correlations among the psychomotor vigilance test (PVT) measures (i.e., reaction times, numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…Pupil diameter is another common way of assessing visual fatigue. Previous studies have shown that a decreased pupil diameter is correlated with a more severe level of visual fatigue (Lee et al, 2013;Naeeri et al, 2021). In this study, the pupil diameter was significantly smaller in the primary mode than in the 360 mode (Figure 4A).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Pupil diameter is another common way of assessing visual fatigue. Previous studies have shown that a decreased pupil diameter is correlated with a more severe level of visual fatigue (Lee et al, 2013;Naeeri et al, 2021). In this study, the pupil diameter was significantly smaller in the primary mode than in the 360 mode (Figure 4A).…”
Section: Discussionsupporting
confidence: 61%
“…However, there was no difference in the average fixation angle between the two modes. An increased fixation duration and decreased fixation frequency are a reflection of visual fatigue, as prolonged fixation time may indicate a need for more time to focus and process the information of interest (Naeeri et al, 2021). Feng et al used fixation frequency and saccade amplitude to assess the effect of far-infrared therapy in relieving visual fatigue and demonstrated the effectiveness of these parameters in assessing visual fatigue (Feng et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…More data should be collected to verify whether the results might accord with bootstrapping results. Future research includes, but are not limited to, investigating sustained attention along with our recent research activities related to physiological measures (Palma Fraga et al, 2020), situation awareness (Argyle et al, 2020), and/or fatigue (Naeeri et al, 2021) that involves prolonged repetitive tasks.…”
Section: Discussionmentioning
confidence: 99%
“…The MVR semantic network app is one of the teaching/learning apps that are being developed at the Human Factors and Simulation Laboratory (Director: Dr. Ziho Kang) at the University of Oklahoma. Other ongoing research activities include, but are not limited to, improving the near real-time analysis capabilities (Kang, 2017; Palma-Fraga et al, 2021), developing algorithms to better visualize the real-time data, investigating the correlations among the various biometric measures (Naeeri et al, 2021), and address the diversified needs among individual based on Universal Design and Learning concept (Rose, 2000).…”
Section: Ongoing and Future Researchmentioning
confidence: 99%